Strategic philanthropy in the post‐Cap‐and‐Trade years: Reviewing U.S. climate and energy foundation funding. (22nd May 2018) - Nisbet, Matthew C.
Abstract : For several decades, philanthropists in the United States have played a behind‐the‐scenes role in framing climate change as a social problem. These foundations have defined climate change primarily as a pollution problem solvable by enacting a price on carbon and by shifting markets in the direction of renewable energy technologies and energy efficiency practices. Funding has favored "insider" groups that push for policy action by way of negotiation, coalition building, and compromise, rather than "outsider" groups that specialize in grassroots organizing. Philanthropists have also placed less priority on funding for other low‐carbon energy sources such as nuclear power, carbon capture and storage, or natural gas, nor have they invested in actions intended to boost societal resilience, protect public health, or to address questions of equity and justice. But in the years following the failure of the 2010 Federal cap and trade bill, a review of available grants from 19 major foundations indicates that philanthropists responded to calls for new directions. Funding shifted to focus on state‐ or municipal‐level mitigation and adaptation actions and to the needs of low‐income/minority communities. Significant funding was also devoted to mobilizing public opinion and to opposing the fossil fuel industry. Nearly a quarter of all funding, however, remained dedicated to promoting renewable energy and efficiency‐related actions with comparatively little funding devoted to other low‐carbon energy technologies. The review of past funding trends provides implications for assessing philanthropic strategy during the Donald J. Trump presidency and beyond. This article is categorized under: Trans‐Disciplinary Perspectives > Regional Reviews The Carbon Economy and Climate Mitigation > Policies, Instruments, Lifestyles, Behavior Abstract : Major Focus Areas for U.S. Climate and Energy Funding, 2011–2015. Note . Based on analysis of 2, 502 publicly reported grants available as of Spring/Summer 2016 which were distributed between 2011 and 2015 by 19 major environmental grantmakers totaling 556, 678, 469. *Low‐carbon energy technologies include funding to make natural gas generation cleaner/safer (8.4 million); to evaluate carbon capture and storage (1.3 million); to promote R&D spending (573, 000), and the role of government in fostering innovation (100, 000). No grants were focused on promoting nuclear energy, though 175, 000 in grants were devoted to opposing nuclear energy for cost and safety reasons.